2012
DOI: 10.1021/nl302015v
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Circuits Based on Bilayer MoS2 Transistors

Abstract: Two-dimensional (2D) materials, such as molybdenum disulfide (MoS 2 ), have been shown to exhibit excellent electrical and optical properties. The semiconducting nature of MoS 2 allows it to overcome the shortcomings of zero-bandgap graphene, while still sharing many of graphene's advantages for electronic and optoelectronic applications. Discrete electronic and optoelectronic components, such as field-effect transistors, sensors and photodetectors made from few-layer MoS 2 show promising performance as potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
1,283
4
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,597 publications
(1,350 citation statements)
references
References 35 publications
32
1,283
4
6
Order By: Relevance
“…An integrated circuit composed of two transistors fabricated on a single flake of MoS 2 was operated as a logical inverter, which converts a logical 0 into a logical 1, and as a logical NOR gate 35 , which is one of the universal gates that can be built in combinations to form all other logic operations 120 . Wang et al also recently demonstrated complex integrated circuits built on bilayer MoS 2 , including an inverter, logical NAND gate, static random access memory and five-stage ring oscillator 121 .…”
Section: Electrical Transport and Devicesmentioning
confidence: 99%
“…An integrated circuit composed of two transistors fabricated on a single flake of MoS 2 was operated as a logical inverter, which converts a logical 0 into a logical 1, and as a logical NOR gate 35 , which is one of the universal gates that can be built in combinations to form all other logic operations 120 . Wang et al also recently demonstrated complex integrated circuits built on bilayer MoS 2 , including an inverter, logical NAND gate, static random access memory and five-stage ring oscillator 121 .…”
Section: Electrical Transport and Devicesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] For example, molybdenum disulphide (MoS2) exhibits an indirect bandgap of 1.2 eV in bulk, but it becomes a direct gap semiconductor (bandgap = 1.8 eV)…”
Section: Table Of Contentmentioning
confidence: 99%
“…4,8 Hence, monolayer MoS2 transistors have been fabricated and these devices have showed excellent current on/off ratios. [10][11][12] MoS2 is known as an n-type semiconductor due to the presence of S vacancies. Another STMD, tungsten diselenide (WSe2), has just started to attract the attention of numerous scientists due to its p-type characteristics.…”
Section: Table Of Contentmentioning
confidence: 99%
“…Two-dimensional (2D) crystals, including graphene, hexagonal boron nitride and transition metal dichalcogenides (TMD), have outstanding properties for developing the next generation of electronic devices [1][2][3][4][5][6][7] . Their extreme thinness, down to a single layer, allows almost perfect electrostatic control of the transistor channel, making them robust to short channel effects and ideal for low power applications 8 .…”
mentioning
confidence: 99%